Merancang Museum Sejarah Kota Seribu Sungai di Kota Banjarmasin - Noor Hamidah; Ilham Akbar (JURNAL TEKNIK, 2021)
Banjarmasin City is one of the cities located in South Kalimantan Province. The Banjarmasin city area is not only surrounded by small rivers, but also by a large river, namely the Barito River in the west, and is divided by the Martapura River in the middle, so that Banjarmasin City is called the City of a Thousand Rivers. Banjarmasin City is an old city that does not yet have a representative city history museum which is expected to be one of the Indonesian Heritage Cities Network. The design of the Thousand Rivers City History Museum is a building that accommodates the historical knots of the early formation of the City of Banjarmasin and the development of the City of Banjarmasin until now, as well as storing historical objects that have been found, such as heirlooms in the form of kris, sabers, and war equipment and household furniture. before. The purpose of this paper is to publish the design of the history museum of the city of a thousand rivers in Banjarmasin City with a green architectural approach. The method uses qualitative methods to examine the function and form of the building through literature studies, comparative studies, and precedent studies as well as field observations. The design approach is green architecture by collecting and using data from literature studies. The result of the design is the application of green architectural principles by utilizing climatic conditions, minimizing solar radiation, and good environmental management in historical museum buildings.